Taxonomic review of the genus Johnius (Perciformes: Sciaenidae) from East Malaysian waters, with comments on newly recorded Johnius species - Hanafi, Norhafiz; Chen, Meng-Hsien; Chang, Chih-Wei; Chao, Ning Labbish; Seah, Ying Giat (Zootaxa, 2024)
In terms of sheer abundance, taxonomic diversity, and species richness, Malaysia has one of the most diverse Sciaenidae in the Indo-West Pacific. Up to ten valid species of the sciaenid fish genus Johnius (e.g., J. amblycephalus (Bleeker, 1855), J. belangerii (Cuvier, 1830), J. borneensis (Bleeker, 1850), J. carouna (Cuvier, 1830), J. coitor (Hamilton, 1822), J. heterolepis Bleeker, 1873, J. macrorhynus (Lal Mohan, 1976), J. plagiostoma (Bleeker, 1849), J. sasakii Hanafi et al., 2022 and J. weberi Hardenberg, 1936), and with additional newly recorded species as J. trewavasae Sasaki, 1992, have been recorded to occur in East Malaysia (Borneo Island) coastal waters. The newly recorded species is a close congener to J. heterolepis Sasaki, 1992 and can be well distinguished by several characters and molecular evidence. The goal of this study is to review the taxonomic status of Johnius species in East Malaysia, Borneo Island, by using a literature review, morphological inference and molecular characters. Principal Component Analysis (PCA) successfully discriminates based on second anal spine length and gill raker length within sampled specimens. A phylogenetic tree based on cytochrome oxidase subunit I (COI) showed intraspecific levels of genetic differentiation within Johnius of East Malaysia, which forms a monophyletic group. Moreover, the new record of Johnius trewavasae in East Malaysia represented that the distribution of the subtropical genus Johnius extended to the southernmost part of the tropical region.